Analysis of the Effect of Temperature on Tire's Durability on Engkel Truck Vehicle - Wayan Suastawa; Ida Bagus Putu Sukadana (Logic : Jurnal Rancang Bangun dan Teknologi, 2019)
Tires are a very important component of a vehicle, a variety of charges are imposed on the tires when the vehicle is stationary or moving. The various loading styles directly rest on the air trapped in the tire, and cause the rise of pressure to flow in accordance with the magnitude of the various forces it receives. The rise in tire pressure mainly occurs when the vehicle is in motion, where the tire gets a compressive force from the constant load of the vehicle and the shock load due to the road contour. High pressure and rising and falling causes heat on the tire which then heat is moved to the rubber tire layer. Besides also because of the heat when the surface of the tire tread rub against the road during acceleration and braking. Assuming that heat is the main cause of tire damage then this study will try to analyze the influence of tire rubber temperature on the ability of work to withstand the air pressure in the tire. The loading received by the tire rubber coating is assumed to be the same as the tensile test that will be applied to the tire when used. This tensile test will be carried out on the rubber tire layer by heat treatment before it is tested. Temperature treatment starts from a temperature of 30 until 110 with a range of 20 degrees, with the expected stress value and the best strain obtained at that temperature range. The tire samples used in this study are two of the most used tire brands on ankle truck trucks which are the most widely used truck types. With tensile test the tire performance is generally very good at low temperature up to 70 degree temperature, above 70 degree temperature tire performance began to decrease due to the increased strain on the tire material so that the ability to resist high pressure by the pneumatic force of the wind inside the tire decreased relative Against the increase in tire temperature.